Influence of Human Resource Management Policy on Customer Loyalty - Mitašiūnaitė, Kamilė (Vilnius University Open Series, 2021)
The business would not be able to achieve the set goals without qualified specialists. Therefore human resource management is one of the most important processes to an organisation. HRM policy aspects – employee motivation and job satisfaction – directly contribute to customer satisfaction and loyalty. The problem is that in today’s business environment, where there is a big rivalry, maintaining customer loyalty becomes a huge task for the business. The aim of this article is to evaluate the impact of human resource management policy on customer loyalty. The article analyses concept of human resource management, evaluates the development of loyal customer behaviour, distinguishes traditional and innovative concepts of human resource management. Also, the article notices a relationship between employee satisfaction and customer satisfaction. Analysis of empirical research level shows the impact of human resource management policy on customer loyalty and provides a research model.